2022
DOI: 10.3389/fnbeh.2022.989011
|View full text |Cite
|
Sign up to set email alerts
|

Work hard, play hard: how sexually differentiated microglia work to shape social play and reproductive behavior

Abstract: Microglia are brain-resident immune cells that play a critical role in synaptic pruning and circuit fine-tuning during development. In the adult brain, microglia actively survey their local environment and mobilize inflammatory responses to signs of damage or infection. Sex differences in microglial gene expression and function across the lifespan have been identified, which play a key role in shaping brain function and behavior. The levels of sex hormones such as androgens, estrogens, and progesterone vary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 98 publications
0
13
0
Order By: Relevance
“…Last, it may be of note that sex hormones have been found to influence microglia morphology and function [ 120 ], and thus are an important consideration when assessing sex differences in immune responses. However, in the context of female stress responses, results from our previous work [ 49 ] showed that CUS significantly increased estrous cycle length with some rats showing a total loss of cycling, effects that began early in the CUS paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Last, it may be of note that sex hormones have been found to influence microglia morphology and function [ 120 ], and thus are an important consideration when assessing sex differences in immune responses. However, in the context of female stress responses, results from our previous work [ 49 ] showed that CUS significantly increased estrous cycle length with some rats showing a total loss of cycling, effects that began early in the CUS paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…While our dataset was too underpowered to quantify sex differences in morphology, our tool could be used to explore known sex differences in microglia in various contexts such as early brain development. (Sullivan & Ciernia, 2022)…”
Section: Discussionmentioning
confidence: 99%
“…Autocrine feedback loops are often utilized by immune cells to self-regulate state, but whether C1q could be acting in this manner is unknown and will be investigated in future studies. In parallel, the critical role of sex differences in microglia has become increasingly recognized (Lynch, 2022; Sullivan & Ciernia, 2022). The novel organelle phenotyping approach established here provides the field with a vital tool that enables investigation of autocrine mechanisms and sex differences in microglia.…”
Section: Discussionmentioning
confidence: 99%